Analysis of Gold Installment Marketing Strategy at Bank Syariah Indonesia Subang Pamanukan Branch Office in Increasing Sales - Agustina, Vina; Karyono, Karyono; Zumara , Zumara (Ecobankers : Journal of Economy and Banking, 2025)
The core issue is understanding the unique marketing strategies and sales advantages of gold installment products at BSI KCP Subang Pamanukan that distinguish it from other Islamic banking branches. This article aims to analyze the marketing strategy of gold installments to increase sales at BSI KCP Subang Pamanukan. Gold Installments is a BSI product that has interest in the community because it offers many benefits for those who want to invest and want stable gold prices. Gold investment is a way to invest now and have benefits in the future. This research method uses a qualitative research method aimed at understanding marketing strategies contextually. Primary data sources are taken from interviews with related parties, secondary data sources are taken from literature in the form of publications and written narratives related to the gold installment marketing strategy. The type of data used is qualitative data. Data collection techniques are taken by interview supported by literature tracking related to the gold installment marketing strategy. Data analysis techniques are in the form of descriptive analysis techniques, analysis techniques on the marketing strategy of gold installment products and increasing their sales. Based on the research conducted, it resulted in a marketing strategy at BSI KCP Subang Pamanukan that the gold installment marketing strategy used is by utilizing social media, distributing brochures, and educating about the benefits of gold investment. Gold sales at BSI KCP Subang Pamanukan experience significant developments every year. The implications of the results of this study are to provide a strategic roadmap for Islamic banking institutions to improve the marketing of gold installment products by offering a targeted approach, flexible options, and customer-centric strategies that can improve sales performance and accessibility of financial products.